The emplacement history of granitic intrusions into the upper crust: Forceful to passive emplacement of the early Miocene Solarya Pluton (NW Turkey) as a case study. (1st October 2019) - Ünal, Alp; Altunkaynak, Şafak; Kamacı, Ömer; Dunkl, Istvan; Benowitz, Jeffrey A.
Graphical abstract: Highlights: The Solarya Pluton (SP) represents a shallow intrusion. The SP has multistage emplacement evolution. Calculated P-T of crystallization for the SP: 797–745 °C and 1.65–0.69 kbar. Multistage emplacement of the SP occurred between 6.1 and 2.4 km depth. Abstract: Post-collisional magmatism in western Anatolia produced several granitic bodies represented by shallow level intrusions. In this study, we present field, geochronology and geothermo-barometry results of the Solarya Pluton (SP, NW Turkey) in order to better understand its emplacement into the different levels of the crust. The SP consists of three main plutonic members showing different textural properties; the northern part of the plutonic body is represented by K-feldspar megacrystalline granodiorite (KFMG) with distinct porphyritic texture and southern part is made up of microgranite-granodiorite (MGG) displaying microgranular texture whereas haplogranite, which displays graphic/granophyric textures, is represented by a thin aureole between the SP and basement rocks. Field relations, petrography and geothermo-barometry studies combined with 40 Ar/ 39 Ar and U-Pb zircon dating results suggest that different members of the SP were emplaced into different levels of crust with different mechanisms. The KFMG ( 40 Ar/ 39 Ar − 23.2 Ma, U-Pb – 21.8 Ma) began its emplacement forcefully in the relatively deeper levels in the crust (av. 1.65 kbar; av. 797 °C; 6.1 km depth). After this stage, MGG ( 40 Ar/ 39 Ar – 22.6 Ma, U-Pb – 21.2 Ma) was passively emplaced into the shallow levels (av. 0.69 kbar; av. 745 °C; 2.4 km depth) via cauldron subsidence and in the latter stages the sheet intrusive rocks (haplogranite 40 Ar/ 39 Ar – 21.6 Ma and hypabyssal association) were emplaced into the ring faults at 1.5 km depth. Forceful to passive emplacement of the SP into the upper crust occurred under Aegean extensional tectonics. Our study contributes to examination of the granite ascent and emplacement within other extensional provinces worldwide.